Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson. (6th January 2015) - Warren, Ben H.; Simberloff, Daniel; Ricklefs, Robert E.; Aguilée, Robin; Condamine, Fabien L.; Gravel, Dominique; Morlon, Hélène; Mouquet, Nicolas; Rosindell, James; Casquet, Juliane; Conti, Elena; Cornuault, Josselin; et al.
Abstract The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, 'An equilibrium theory of insular zoogeography', was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.